"Impact of Tobacco Ban on Smoking Prevalence and Related Health Outcomes" (International Journal of Food and Nutritional Sciences, 2022)
This study examines the effects of a comprehensive tobacco ban on smoking prevalence and associated health outcomes within a defined population. The research employs a mixed-method approach, incorporating quantitative analysis of population-level data and qualitative assessments of individual experiences. The study leverages longitudinal data spanning pre- and post-ban periods to capture trends in smoking behavior and health indicators. Initial findings reveal a significant reduction in smoking prevalence following the implementation of the tobacco ban. Statistical analysis indicates a sustained decline in the proportion of smokers, with notable reductions observed across diverse demographic groups. Concurrently, a parallel examination of health outcomes demonstrates positive shifts in indicators related to respiratory health, cardiovascular well-being, and overall mortality rates.